Level of Patient Satisfaction with Antenatal Services at Tutun Sehati Clinic - Rhina Chairani Lubis; Lili Nurmaliza; Febri Yusnanda; Tika Ayu Pratiwi (PT Inovasi Pratama Internasional, 2023)
The health sector has an important role in improving the health of the people in Indonesia. And one of the responsibilities in the world of health is to ensure the availability of quality health services and also have high quality. One of the characteristics of quality and quality health services is the satisfaction of antenatal care patients carried out in an effort to improve service quality at the Tutun Sehati Clinic. The research was conducted using qualitative research with sampling methods as well as research instruments in the form of questionnaires and interviews. The samples taken were samples from pregnant women who had ANC examinations at the Tutun Sehati Clinic. The results of the study show patient satisfaction related to the dimensions of service quality and also patient satisfaction at the Tutun Sehati Clinic. Based on the results of the research and also this discussion, it is concluded that there are several suggestions from the researchers which are taken into consideration that improving services at the clinic for Antenatal Care services must be continued. This is to provide quality and service quality to patients, especially pregnant women who use these services during their pregnancy check-ups.